Review of DC-AC converters for photovoltaic conversion chains - Mounir Bouzguenda; Tarek Selmi (International Journal of Power Electronics and Drive Systems (IJPEDS), 2021)
This paper is devoted to the state of the art in photovoltaic (PV) conversion chains and their architectures. Two major characteristics are considered to classify these chains. These are the galvanic isolation and the number of stages; characteristics generally localized around the DC-AC converter (inverter) at the end of the PV conversion chain. Therefore, this paper deals with a comprehensive review of the different inverter topologies that can be integrated into PV conversion chains, distinguishing between the transformer based and the transformer-less conversion chains. The paper demonstrates that to this date, transformer-based inverters are very common and widely used, have a long record of accomplishment as a component of solar energy systems, in particular for residential applications because of their greater efficiency, smaller size, and lower costs. Nevertheless, transformer-less chains are touted with some problems and shortcomings.  Moreover, solar energy storage devices, wireless charging systems in stations and along the highways require the re-examination of the existing solar PV conversion chains, their architectures and possibly new conversion chains suitable for all distributed generation including electric cars and storage devices.